Characterization of polarization-independent phase modulation method for practical plug and play quantum cryptography. (22nd October 2015) - Kwon, Osung; Lee, Min-Soo; Woo, Min Ki; Park, Byung Kwon; Kim, Il Young; Kim, Yong-Su; Han, Sang-Wook; Moon, Sung
Abstract: We characterized a polarization-independent phase modulation method, called double phase modulation, for a practical plug and play quantum key distribution (QKD) system. Following investigation of theoretical backgrounds, we applied the method to the practical QKD system and characterized the performance through comparing single phase modulation (SPM) and double phase modulation. Consequently, we obtained repeatable and accurate phase modulation confirmed by high visibility single photon interference even for input signals with arbitrary polarization. Further, the results show that only 80% of the bias voltage required in the case of single phase modulation is needed to obtain the target amount of phase modulation.